The use of lip bumper to overcome lower lip sucking habit - Budhiawan, Marcella; Krisnawati, K. (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2010)
The patient was a 16-year-old girl with a lower lip sucking habit with increased overjet, maxillary and mandibular generalized spacing. Hyperactivity of the mentalis muscle and deepening of the labiomental sulcus because of the abnormal sucking habit was observed. Orthodontic treatment was started with a lip bumper appliance to break the lower sucking habit and continued with fixed orthodontic mechanotherapy. The lip bumper appliance therapy resulted in the elimination of the lower lip sucking habit, musculus mentalis hyperactivity, and labiomental strain, and also an overjet reduction. The use functional appliance in the treatment of malocclusions must be carefully selected according to the requirement of the case. It must be understood that the action of the mentalis muscle was the primary activator of the bumper.